The Analysis of Supply Chain of Mulu Bebe Banana in East Sahu Sub-District - Zakeus Dadi; Musdhalifah Kholil (Sangia Publishing, 2020)
The purpose of this study is to find out the Mulu bebe banana supply chain mechanism in East Sahu Sub-District, to find out the marketing distribution of Mulu bebe banana in East Sahu Sub- District and to find out the marketing margins in each supply chain of Mulu bebe banana. The study was conducted in East Sahu Sub-district through observation, questionnaires, direct interviews with the agribusiness perpetrators of the Mulu bebe banana in 2018. The sample selection was carried out by stratified sampling and total sample is 73 respondents. The results showed that there were three flow mechanisms, first is the information flow, product flow and financial flow. There were two marketing distribution of Mulu bebe banana in East Sahu sub-district used by farmers. First, farmers to consumers and second is farmers to village collection traders to retailers then to consumers. While the total marketing margins obtained by collectors and retailers in marketing distributin II in grade A and grade B mulu bebe bananas are Rp. 30,000, while the marketing margin obtained by collectors and retailers in grade C of Mulu bebe banana is Rp. 25,000.